Reverse osmosis powered by concentrating solar power (CSP): a case study for Trapani, Sicily - Ahmed, Mahran K. A. (2015)
The objective of this paper is to analyse the physical performance of two technologies in a water and electricity co-generation scheme: Concentrated Solar Power (CSP) plant coupled to a Reverse Osmosis (RO) unit for a location in the city of Trapani, in southern Italy. The modelled system is compared with the results of another study [2], in which a Multi-Effect Desalination (MED) is powered by a CSP plant for the same location in Italy, using as reference an existing stand-alone gas powered MED plant located at Trapani [3] (which has operated until very recently). The overall aim is to assess and compare these two cogeneration schemes, using as reference the existing MED plant. This work was conducted using as the main simulation tool: the System Advisor Model (SAM) developed by the US National Renewable Energy Laboratory (NREL); a recent upgrade to SAM made available to this work through Laboratório Nacional de Energia e Geologia I.P. (LNEG); and the Reverse Osmosis System Analysis (ROSA) developed by the Dow Chemical Company. A technical visit to a real commercial RO plant in the south of Portugal (Alvor) was conducted, and the data gathered was used in the validation of the ROSA model. The results for the Trapani case study show that the CSP-RO arrangement has the capability to produce ~50% of the total production of the full scale plant at Trapani, if operated at nominal capacity, year round. Also, the CSP-RO system provides ~20% more electricity and water than the CSP-MED system throughout the studied period of one year. The two co-generation schemes provide promising potential to fight the issues related to fresh water shortages and dependency on fossil fuelled desalination. Thus, they can aid in decreasing the effects associated with CO2 emissions and climate change.